2000
DOI: 10.1074/jbc.m002248200
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Enhances Endothelial Nitric-oxide Synthase Activity by Increasing Intracellular Tetrahydrobiopterin

Abstract: Ascorbic acid enhances NO bioactivity in patients with vascular disease through unclear mechanism(s).We investigated the role of intracellular ascorbic acid in endothelium-derived NO bioactivity. Incubation of porcine aortic endothelial cells (PAECs) with ascorbic acid produced time-and dose-dependent intracellular ascorbic acid accumulation that enhanced NO bioactivity by 70% measured as A23187-induced cGMP accumulation. This effect was due to enhanced NO production because ascorbate stimulated both PAEC nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
189
3
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 337 publications
(211 citation statements)
references
References 67 publications
14
189
3
5
Order By: Relevance
“…In addition, with regard to reactive nitrogen species, we found that the treatment of NO synthase inhibitor L-NAME reduced the extravasation of Evans Blue and IgG, despite no statistical significance ( Figures 4P and 5J). However, ascorbic acid, which protected the BBB in our model, has been shown to be capable of increasing the NO production and bioactivity without affecting the NO synthase expression (Heller et al, 2001;Huang et al, 2000). Actually, up to now, a number of reports on the role of NO in the BBB modulation are also contradictory (Boje and Lakhman, 2000;Kuhlmann et al, 2006;Wong et al, 2004).…”
Section: Discussionmentioning
confidence: 67%
“…In addition, with regard to reactive nitrogen species, we found that the treatment of NO synthase inhibitor L-NAME reduced the extravasation of Evans Blue and IgG, despite no statistical significance ( Figures 4P and 5J). However, ascorbic acid, which protected the BBB in our model, has been shown to be capable of increasing the NO production and bioactivity without affecting the NO synthase expression (Heller et al, 2001;Huang et al, 2000). Actually, up to now, a number of reports on the role of NO in the BBB modulation are also contradictory (Boje and Lakhman, 2000;Kuhlmann et al, 2006;Wong et al, 2004).…”
Section: Discussionmentioning
confidence: 67%
“…However, along with other studies [40,41], we found no evidence to support this finding. Other potential mechanisms whereby CoQ could have improved endothelial function in the brachial artery involve reduction in the cellular levels of asymmetric dimethyl-arginine and AGEs [31,42], as well as an increase in the bioavailability of tetrahydrobiopterin [43] and glutathione [44]. Normalization of mitochondrial superoxide production could be central to these mechanisms and to an anti-inflammatory effect of CoQ [45].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate levels of co-factors and L-arginine can result in NOS dysfunction and uncoupling, altering NOS output from NO to O 2 ·- (Vasquez-Vivar et al 1998;Huang et al 2000). Dysfunction of NOS also can occur with oxidation of the heme complex or BH 4 by ONOO -also resulting in uncoupled NOS (Figure 2.7, (Huang et al 2000;Harrison et al 2003b).…”
Section: Nos (Enos) and Inducible Nos (Inos) In Addition There Is Tmentioning
confidence: 99%